Managing usability evaluation practices in agile development environments - Aziz Bin Deraman; Fouad Abdulameer Salman (Institute of Advanced Engineering and Science, 2019)
Usability evaluation is a core usability activity that minimizes risks and improves product quality. The returns from usability evaluation are undeniable. Neglecting such evaluation at the development stage negatively affects software usability. In this paper, the authors develop a software management tool used to incorporate usability evaluation activities into the agile environment. Using this tool, agile development teams can manage a continuous evaluation process, tightly coupled with the development process, allowing them to develop high quality software products with adequate level of usability. The tool was evaluated through verification, followed by the validation on satisfaction. The evaluation results show that the tool increased software development practitioner satisfaction and is practical for supporting usability work in software projects.